Cancer co-occurrence patterns in Parkinson's disease and multiple sclerosis—Do they mirror immune system imbalances?. (October 2016) - Ajdacic-Gross, Vladeta; Rodgers, Stephanie; Aleksandrowicz, Aleksandra; Mutsch, Margot; Steinemann, Nina; von Wyl, Viktor; von Känel, Roland; Bopp, Matthias
Highlights: Patterns of cancer mortality in Parkinson's disease and MS were examined. PD and MS shared a lower risk of lung cancer and a higher risk of breast cancer. This is similar in schizophrenia, but opposite in RA and in immunosuppression. Cancer co-occurrence patterns diseases can mirror immune system imbalances. Abstract: Background: To examine the site-specific cancer mortality among deaths registered with Parkinson's disease (PD) and multiple sclerosis (MS). We focused on the patterns related to the most frequent cancers. Methods: We analyzed Swiss mortality data over a 39-year period (1969–2007), using a statistical approach applicable to unique daabases, i.e. when no linkage with morbidity databases or disease registries is possible. It was based on a case-control design with bootstrapping to derive standardized mortality ratios (SMR). The cases were defined by the cancer-PD or cancer-MS co-registrations, whereas the controls were drawn from the remaining records with cancer deaths (matching criteria: sex, age, language region of Switzerland, subperiods 1969–1981, 1982–1994, 1995–2007). Results: For PD we found lower SMRs in lung and liver cancer and higher SMRs in melanoma/skin cancer, and in cancers of breast and prostate. As for MS, the SMR in lung cancer was lower than expected, whereas SMRs in colorectal, breast and bladder cancer were higher. Conclusions: A common pattern of associations can be observed in PD and MS, with a lower risk of lung cancer and higher risk of breast cancer than expected. Thus, PD and MS resemble other conditions with similar (schizophrenia) or reversed patterns (rheumatoid arthritis, immunosuppression after organ transplantation).